Exploring the Factors that Influence Female Students’ Decision to (Not) Enrol in Elective Physical Education: A Private School Case Study - Kiley, Jill; Robinson, Daniel Bruce (Alberta Journal of Educational Research, 2016)
This article presents the results from a qualitative case study that examined the influencers upon a somewhat unique group of female students who opted out of elective physical education (PE). More specifically, this study focused upon female students attending an affluent private school, investigating why—when they transitioned from middle school to senior high school and PE became optional—they opted out of the class. Employing a research design that relied principally upon in-depth interviews, seven themes emerged from the students’ stories: perspectives on policy and PE programming, co-ed problems; friends’ influence, parental support for opting out, A+ academic achievement, free time and electives, and adequate physical activity accumulation outside of school. By considering these themes, particularly as they align with an Ecological Systems Theory, or EST (Bronfenbrenner, 1977) social-ecological framework, it is possible to more fully comprehend contributing influencers to these students’ decisions. Moreover, with this comprehension, we offer suggestions for future practice and inquiry. Cet article présente les résultats d’une étude de cas qualitative qui a examiné les facteurs qui influencent un groupe quelque peu unique d’étudiantes qui avaient choisi de ne pas s’inscrire au cours d’éducation physique facultatif. Plus précisément, cette étude porte sur les raisons pour lesquelles les étudiantes d’une école privée pour familles aisées, lors de leur transition de l’école élémentaire vers l’école secondaire où le cours d’éducation physique est dorénavant facultatif, ont décidé de ne pas s’y inscrire. La recherche repose sur une conception qui s’appuie principalement sur les entrevues détaillées. Sept thèmes découlent des récits des étudiantes : des perspectives sur la politique et la programmation du cours d’éducation physique; des problèmes liées aux cours mixtes; l’influence des amis; l’appui parental devant le choix de ne pas s’inscrire; une rendement académique de A+; le temps libre et les cours facultatifs; et suffisamment d’activité physique à l’extérieur de l’école. L’étude de ces thèmes et notamment la mesure dans laquelle ils correspondent à la Théorie des systèmes écologiques (Brofenbrenner, 1977) aide à mieux comprendre les facteurs qui influencent les décisions de ces étudiantes. Nous appuyant sur ces conclusions, nous offrons des suggestions pour la pratique et la recherche à l’avenir.